Picturing Chinatown : art and orientalism in San Francisco - Lee, Anthony W., 1960- (Ahmanson Murphy fine arts imprint., 2001)
Throughout European history, Jews have been associated with commerce and the money trade, rendered both visible and vulnerable, like Shylock, by their economic distinctiveness. This is the story of Jewish perceptions of this economic difference and its effect on modern Jewish identity.